The Discourses of “Wanted sa Radyo’s” VAW-related Episodes - P. Lagusad Jr., Rodrigo; Fajardo, Kim Bernard G. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Today, the media holds an indisputable influence over public opinion, serving as a formidable tool for information dissemination, persuasion, and the molding of collective perspectives (Allen, 2017; Impe, 2019). This study conducted an in-depth examination of the discourse within the Philippines’ Radyo 5 program, 'Wanted sa Radyo,' hosted by broadcaster and senator, Raffy Tulfo (Afinidad-Bernardo, 2019). Recognized as a public service program aiming to assist those in need, this research specifically scrutinized episodes that shed light on the distressing issue of violence against women (UN Women, 2023). Through a comprehensive utilization of textual analysis as the methodology (McKee, 2003; Luo, 2019), this study aimed to ascertain how the program presented and addressed these sensitive issues during live broadcasts. The findings of this research showed that the program exhibited sensitivity when discussing the delicate topics that surrounded violence against women (GMA Integrated News, 2023). With careful consideration and tactful handling of such issues, Raffy Tulfo, the program's host, showcased a remarkable empathetic approach toward complainants while impartially interrogating the accused (Raffy Tulfo in Action, 2018). As a result, it became evident that 'Wanted sa Radyo' remained true to its core mission as a public service platform (ABS-CBN News, 2022). Shedding light on the effectiveness of public service program in amplifying marginalized voices, addressing pressing social concerns, and ultimately contributing to the betterment of society (Impe, 2019; Atkin, 2013). This aligns with the broader goals of media studies in understanding and evaluating the impact of media on society (Abowitz et al., 2010; Spitulnik, 1993).